Analysis of The Effectiveness of the Wastewater Treatment Installation and The Quality of Liquid Waste at XYZ Hospital in Cilegon City - Safril Kartika Wardana; Syariful Maliki; Fikri Maulana; Dadi Cahyadi (Universitas Muhammadiyah Purwokerto, 2025)
WWTP in Cilegon City demonstrates a strong commitment to controlling environmental pollution through the operation of its Wastewater Treatment Plant (WWTP). This study aims to evaluate the quality of treated effluent and assess the effectiveness of the WWTP in reducing key pollution parameters: Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Total Suspended Solids (TSS), and free ammonia (NH₃-free). Wastewater samples were collected from the WWTP inlet every three months and from the outlet monthly, each consisting of 2 liters, and analyzed in accordance with Indonesian environmental standards (PERMENLH No. 5 of 2014). The analysis showed that the treated effluent met regulatory quality standards, with pollutant removal efficiencies reaching 96.55% for TSS, 87.28% for BOD, 79.86% for COD, and 99.76% for NH₃-free. These findings indicate that the WWTP functions effectively, with high removal efficiency for both organic and inorganic pollutants, thus ensuring compliance with environmental regulations and highlighting its success as a model for Hospital wastewater management.